Determining Arsenic Distribution in Urban Soils: A Comparison with Nonurban Soils - Tait Chirenje; L.Q. Ma; E.J. Zillioux (The Scientific World Journal)
There are many challenges in the determination of arsenic background concentrations in soils. However, these challenges are magnified when those determinations are carried out on urban soils. Irrespective of this, it is important to correctly identify and understand the extent of pollution in order to provide efficient preventative, remedial actions and cost-effective management of contaminated areas. This review paper discusses the factors that make the determination of arsenic background concentrations in urban areas different from similar determinations in nonurban areas. It also proposes solutions, where applicable, that are based on experience in determining arsenic background concentrations in both urban and nonurban areas in Florida, and from other studies in the literature. Urban soils are considerably different from nonurban areas because they have significant human disturbance, making them more difficult to study. They are characterized by high spatial and temporal variability, compaction, and modified chemical and physical characteristics. These differences have to be addressed during site selection, sample collection, and statistical analyses when determining arsenic distribution.